(untitled) (Asian Education Studies, 2018)
Subject of the study is the issue of effectiveness improvement within the education of socially disadvantaged pupils originating from marginalized Romany communities in younger school age in Slovakia through the stimulation of deficit cognitive functions, in the process of development of their communicative and reading competence. Main objective of the paper is presentation of stimulation programme proposal for development of cognitive functions (sorting, sequential auditory memory, short-term visual memory, addition of sequential patterns, perspective taking, and verbal planning) based on the methodology of dynamic testing of cognitive functions according to diagnostic measure ACFS (Application of Cognitive Functions Scale, Czech version, Lidz, Jepsen, Krejčová, 2014), for work with the adaption of Romany literary text (folk-tale) Children of the Sun from D. Hivešová-Šilanová. Children protagonist from socially disadvantaged backgrounds – Roma boy Lavutaris very sensitively perceives social differences in the intentions of own, minority society, as well as in their co-existence with the major society, and thus the implementation of cognitive stimulation programme takes on significance not only in the process of communicative and reading competence of socially disadvantaged pupils in younger school age, but within the multicultural and emotional education of all the pupils in terms of school inclusion in Slovakia as well.